GROCERIES SUPPLIER SELECTION ANALYSIS TO MEET THE NEEDS OF FOOD AND BEVERAGE DEPARTMENT AT THE MELIA BALI INDONESIA HOTEL - I Komang Artha Darmaja; I Nyoman Meirejeki; Made Sudiarta (Politeknik Negeri Bali, 2018)
Food and Beverage Department requires suppliers who can provide food and beverage ingredients. The Food and Beverage Department in selecting suppliers is assisted by the Purchasing division of Accounting Department. The Purchasing division is responsible for the procurement of items needed by every department in the hotel, therefore, making supplier selection is their responsibility. The problems of this study are (1) what is the procedure for selecting groceries suppliers? (2) among the existing criteria, which are the main criteria in selecting groceries suppliers for the Food and Beverage Department needs at the Melia Bali Indonesia Hotel? This study is a quantitative research. The primary data were collected by questionnaire, interview, observation, and document study. Snowball sampling method was used in this study to determine the sampling with the number of the sampling is 8 respondents. The procedure for groceries supplier selection involves Purchasing division and Food and Beverage Department. The documents completeness, price, quality, delivery service, and product inventory from the supplier are used as consideration to choose the best supplier. The supplier approval is made by the product user and Purchasing division. Based on the results of the questionnaire, descriptive statistical analysis technique was used using simple quantification which showed that the main criteria considered by groceries suppliers to meet the needs of the Food and Beverage Department was the documents completeness with an average of 4.75 which was at a very good interval.